EFFICACY OF INVASIVE GREEN MANURES AND MYCORRHIZA ON GROWTH AND YIELD OF DIFFERENT LEGUMES CROPS AND STUDY THEIR ANTIMICROBIAL PROPERTIES (Scientific World, 2015)
Application of the invasive green manure (locally available Lantana camara, Eupatorium adenophorum) is an essential means to maintain soil fertility, soil structure and stimulate biological activities extensively. In this present study field trial of Lentil and Rajma were conducted in Kosebali Divison of Rampur, Chitwan district. Mycorrhiza was isolated from agricultural soil by sugar decantation method and mass production with the help of onion plant. Leaves of Lantana camara and Eupatorium adenophorum were collected and shed dried and grinded on powdered form. The treatments with green manures and mycorrhizae showed higher yield than the control in case of Lentil field trial. In case of Rajma field trial, length of stems and dry seed formation was higher in Eupatorium adenophorum and followed by Lantana camara, chemical fertilizer, control and mycorrhiza. Mycorrhizal spores were found higher in Lantana camara followed by Eupatorium adenophorum, mycorrhizal, chemical fertilizer and control. The number of mycorrhizal spores was found higher in case of Lantana camara followed by Eupatorium adenophorum, mycorrhiza, compost, chemical fertilizer and control. The percentage of seedless and low seeded pods were found higher on control followed by compost, chemical fertilizer, Lantana camara, Eupatorium adenophorum and mycorrhiza.Scientific World, Vol. 12, No. 12, September 2014, page 65-69